2005
DOI: 10.1111/j.1348-0421.2005.tb03632.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Cholera Toxin B Subunit Activates Dendritic Cells and Enhances Antitumor Immunity

Abstract: Activation of dendritic cells (DC) is crucial for priming of cytotoxic T lymphocytes (CTL), which have a critical role in tumor immunity, and it is considered that adjuvants are necessary for activation of DC and for enhancement of cellular immunity. In this study, we examined an adjuvant capacity of recombinant cholera toxin B subunit (rCTB), which is non‐toxic subunit of cholera toxin, on maturation of murine splenic DC. After the in vitro incubation of DC with rCTB, the expression of MHC class II and B7–2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
17
2
Order By: Relevance
“…These results are in agreement with a previous observation made in the murine system, whereby free CTB, differently from CTB conjugated with antigens, was found not to enhance the cell-surface levels of CD80 and CD86 [7]. However, they are in contrast with other data reporting the effect of CTB on splenic murine DC, which demonstrated that the in vitro incubation of murine DC with rCTB induces up-regulation of the expression of MHC class II and CD86 on DC and an increased secretion of IL-12 [29]. Reasons for these discrepancies are not easily recognized, but heterogeneity of myeloid murine DC and their state of maturation might account for the contrasting results observed in the murine system [30,31].…”
Section: Discussioncontrasting
confidence: 78%
“…These results are in agreement with a previous observation made in the murine system, whereby free CTB, differently from CTB conjugated with antigens, was found not to enhance the cell-surface levels of CD80 and CD86 [7]. However, they are in contrast with other data reporting the effect of CTB on splenic murine DC, which demonstrated that the in vitro incubation of murine DC with rCTB induces up-regulation of the expression of MHC class II and CD86 on DC and an increased secretion of IL-12 [29]. Reasons for these discrepancies are not easily recognized, but heterogeneity of myeloid murine DC and their state of maturation might account for the contrasting results observed in the murine system [30,31].…”
Section: Discussioncontrasting
confidence: 78%
“…We also observed that CT upregulated costimulatory molecules CD80 and CD86, and MHC II on DCs, in agreement with previous reports. 21 Thus, these PE antigen-loaded DCs would have acquired the capability to generate the necessary signals for PEspecific T H 2 cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…CTB exhibits differential consequences in stimulated DCs or conjugation to antigens. It has been shown to significantly enhance the immunogenicity of linked exogenous antigens 12 through induction of DC activation, 13,14 enhanced B-cell and T-cell responses 15 , and decrease the dose of antigen. 12 Based on our previous studies, we found that the efficacy of immune responses induced by vaccine antigen depended on the level of inflammation or the strength of innate immunity induced by co-vaccinated adjuvants.…”
Section: Introductionmentioning
confidence: 99%